Resolution numerique des equations de transport des tensions de Reynolds en ecoulements turbulents confines en rotation - Elena, Laurent; Schiestel, Roland (European Journal of Computational Mechanics, 1995)
A numerical procedure for Reynolds stress transport equations is presented using a semi staggered grid. The system formed by the stress equations is solved by point implicit method in order to preserve the so important couplings for numerical stability. The method is then applied for two different turbulence models to the prediction of the turbulent flow due to a rotating disk. The mean flow prediction are in good agreement with the experimental data, while for the turbulent field some discrepancies remain.